Photocatalytic reduction of Cr(vi) by graphene oxide materials under sunlight or visible light: the effects of low-molecular-weight chemicals. Issue 8 (20th July 2020) - Wu, Shang-Shing; Hou, Wen-Che; Wang, David K.
Abstract : GO rapidly photocatalyzes the reduction of Cr(vi ) utilizing sunlight in the presence of oxalate that acts as an electron donor and chelating agent. Abstract : We present a new, rapid method to photocatalytically reduce the highly toxic Cr(vi ) to Cr(iii ) by a graphene oxide (GO) photocatalyst utilizing renewable sunlight or visible light. We found that GO can photoreduce Cr(vi ) (0.32 mM) with 35.8 ± 4.8% conversion in 120 min of solar irradiation and that oxalate significantly accelerates this reaction (85.6 ± 5.4% in 30 min). The photocatalytic reactivity of GO is comparable with or superior to that of P25 TiO2 under sunlight or visible light irradiation and is among the best in existing photocatalytic Cr(vi ) reduction systems involving carbon-based nanomaterials. In contrast, the photoreduction of Cr(vi ) using reduced GO greatly declines with 8.5 ± 1.4% conversion in 30 min. The efficacy of low-molecular-weight (LMW) chemicals follows the order: oxalate > EDTA > formate ≈ acetate ≈ methanol ≈ no addition. The measured molar ratio of oxalate consumed by reduced Cr(vi ) is 1.6 ± 0.26, consistent with oxalate as an electron donor. The UV-visible absorbance spectrum indicates the formation of the oxalate–Cr(v ) complex that could facilitate Cr(vi ) photoreduction. Chromium speciation studies using the HPLC-ICP-MS method quantitatively confirmed that the increase of Cr(iii ) species was directly attributed to Cr(vi ) photoreduction. The photocatalytic reduction by GO shows good stability in real wastewater samples and after three cycles of reaction. Our results indicate that GO is a simple and promising new photocatalyst toward Cr(vi ) reduction.